The Economics of Internal Organization: Exit and Voice in Relation to Markets and Hierarchies - Williamson, Oliver E. (American Economic Review, 1976)
The economics of internal organization is concerned with two closely related issues. As contrasted with received micro theory, which is preoccupied with the operation of markets (whence the firm exists mainly as an analytical convenience), the economics of internal organization emphasizes that market organization and hierarchical (internal) organization are alternative–sometimes substitute but also complementary-means of executing transactions. The object is to assign transactions to markets and hierarchies so as to achieve a most preferred (usually least cost) result, where this is judged principally in terms of transaction costs. Whereas conventional micro theory is relatively unconcerned with assessing the merits of executing transactions by one mode rather than another (partly because prevailinig modes are commonly held to be optimal), the economics of internal organization regards the assignment of transactions to markets and hierarchies as intrinsically interesting. The second issue of importance to the study of the economics of internal organization concerns organization form. Just as market structure matters in assessing the efficacy of price mediated transactions in the market place, so internal structure matters in assessing the properties of administrative organization. The hierarchical decomposition of tasks and the types of internal control processes that are employed are both germane to an assessment of internal organization. This paper sets out some of the leading attributes of Albert Hirschman's Exit, Voice and Loyalty (EVL) (1970) and my Markets and Hierarchies (MH) (1975). As will be evident, both sometimes complement received micro theory where conventional theory is silent or ambivalent. In other respects, however, EVL and MH offer substitute ways of interpreting or dealing with issues that fall within the range of received micro theory -or straightforward applications thereof.' EVL and MH also bear complementary and substitute relations to each other.2